USP12 positively regulates M‐MDSC function to inhibit antitumour immunity through deubiquitinating and stabilizing p65. Issue 4 (8th August 2022) - Zhan, Xiaoxia; He, Qiuying; Sheng, Junli; Jiang, Xiaobing; Lin, Letao; Huang, Yulan; He, Shitong; Chen, Yitian; Li, Laisheng; Zeng, Zhijie; Hu, Shengfeng; Wang, Peng; et al.
Abstract: The relative abundance of myeloid‐derived suppressor cells (MDSCs) compared to cytotoxic T cells determines the outcomes of diseases and the efficacy of immunotherapy. Ubiquitin‐specific peptidase 12 (USP12), a member of the USP family of deubiquitinases, targets multiple signalling pathways and regulates diverse biological processes, including cell proliferation and survival. It is well known that ubiquitylation is an important mechanism for regulating the immune response. However, it is unclear whether USP12 regulates tumour growth by influencing MDSCs. In the present study, we reported that USP12 deficiency decreased infiltration and impaired the suppressor function of monocytic (M)‐MDSCs, resulting in increased CD8 + T‐cell response and decelerated tumour growth. USP12‐knockout M‐MDSCs were less potent in inhibiting the proliferation of CD8 + T cells and their ability to secrete IFN‐γ. Furthermore, USP12 deficiency inhibited the suppressor function of M‐MDSCs by downregulating the negative regulatory molecules inducible nitric oxide synthase and PD‐L1, through deubiquitinating and stabilizing p65. Our results suggest that USP12 is a positive regulator of M‐MDSCs and may serve as a potential target for antitumor therapy. Abstract : USP12 deficiency decreased infiltration and impaired the suppressor function of monocytic myeloid‐derived suppressor cells (M‐MDSCs), resulting in increased CD8 + T‐cell response and decelerated tumor growth. USP12‐knockout M‐MDSCs were less potent in inhibiting the proliferation of CD8 + T cells and their ability to secrete IFN‐γ. USP12 deficiency inhibited the suppressor function of M‐MDSCs by downregulating the negative regulatory molecules iNOS and PD‐L1, through deubiquitinating and stabilizing p65.